Sustainable development goals and agricultural service subscriptions: Consumer behaviors in Cebu, Philippines - JAKE JOSHUA C. GARCES (Asian Journal of Agriculture, 2026)
Abstract. Garces JJC. 2026. Sustainable development goals and agricultural service subscriptions: Consumer behaviors in Cebu, Philippines. Asian J Agric 10: g100101. https://doi.org/10.13057/asianjagric/g100101 As the Philippines faces growing challenges in food insecurity and unsustainable consumption, this study explores why many Cebuano consumers who support the Sustainable Development Goals (SDGs) are not actively participating in agricultural subscription services. These services, which connect consumers directly with local farmers, offer a promising way to promote sustainable food systems. Through a survey of 488 respondents across Cebu Island, the study identified three types of consumers: (i) General subscribers, (ii) Price-conscious consumers, and (iii) Quality-focused consumers. General subscribers showed the strongest sustainability alignment, with 58% actively minimizing food waste, compared to 29% of price-conscious consumers and 34% of quality-focused consumers, while regression and chi-square results identified age group, marital status, and education level as significant determinants of subscription. These findings conclude that consumer subscription behaviors are shaped not only by affordability and product quality considerations but also by the degree of alignment with sustainability values, emphasizing that stronger integration of SDG-oriented practices corresponds to more consistent participation in agricultural subscription services.